Analysis of Knowledge, Attitude, and Kia Book Utilization Regarding Emergency Signs and Symptoms in Pregnancy - Keswara, Nila Widya; Laksono, Bayu Budi (Babali Publisher, 2024)
Introduction: The Maternal Mortality Rate (MMR) is still high and far from the target of the Development Goals Sustainable Development Goals (SDGs). There are 70 cases per 100,000 live births in 2030. MMR has not dropped yet. The KIA book is a tool for early detection of health disorders or problems. This research aimed to investigate an analysis between knowledge, attitude, and utilization of the KIA book regarding emergency signs and symptoms in pregnancy. Methods: This quantitative research, using a cross-sectional design approach, obtained 80 pregnant women at Bandungrejosari Malang from January 19th to February 9th, 2023.Results: The positive correlation between the level of knowledge and utilization is shown by a P value of 0.000 with r=0.475. Attitude and utilization variables show similar results, with a P value of 0.013 with r = 0.263. The knowledge variable directly affects the utilization variable with P value=0.042 and OR=3.328. Conclusion: Knowledge simultaneously influences the utilization of KIA books on Posyandu regarding emergency signs and symptoms in pregnancy as well as attitudes. Good knowledge will encourage better health attitudes and behavior. Attitudes contribute to behavior, but they must be supported by other factors such as mentoring and motivation.